Teaching reading comprehension by using short stories - Hasbaini Hasbaini; Abdul Manan (Universitas Syiah Kuala, 2017)
This research was intended to figure out the effectiveness of the use of short stories in teaching reading comprehension to enhance the quality of students’ reading to the first semester students of Tarbiyah of Muhammadiyah University of Aceh. The mayor principle of conducting this research was to investigate whether or not the students in the experimental group taught by using short stories would produce a higher achievement than those of the control group taught by using conventional study. To find out the effectiveness of the use of short stories, the pre-test and the post-test were given for those groups. The result of data analysis demonstrated that there was a significant difference on students’ achievement from both groups proved by the average of the post-test’s score. As a result, the score of the post-test of the experimental group is higher than that of the control group (80:65) by which the gained score for t-test was 8 while the value for t-table was 1,684 at the level of significance 0,05. It means that t-score was higher than t-table (8 1,684). It can be concluded that the students who were taught by using short stories had a better achievement in reading comprehension than those who taught by using conventional study.